Numerical investigation of the Euler turbomachinery equation and analysis of the impact of the impeller design on the fan performance by an optimization study - Fritsche, Manuel; Epple, Philipp; Gast, Stefan; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2019)
The working machines such as fans, blowers and pumps are often used for transporting fluids in technical systems. The rotating impeller is used for energy conversion of mechanical work into hydraulic work. Leonhard Euler published this relation of energy conversion in 1752-1756 and is still used today for the basic design of turbomachinery. In the present work, the Euler-Equation is described and presented in detail. Furthermore, a simplified parameterized blade channel of a centrifugal impeller is investigated with numerical simulation methods. The theoretical Euler-Equation is compared and validated with the numerical CFD-results. Based on an extensive CFD-optimization study, the impact of the impeller design parameters on the fan performance has been investigated. For this purpose, the blade shape and the operating conditions (speed and volume flow rate) were systematically varied. After an extensive grid study, the influence of the blade channel contour on the fan performance was investigated. The results of the study are presented in detail.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Blade; Euler-Equation; Fan; Turbomachinery